A comparative study of stress among medical and dental students - Adhikari, Bijaya; Maharjan, Niroj; Baskota, Grishma; Bhaila, Archana; Shrestha, Hari Sundar (Asian Journal of Medical Sciences, 2021)
Background: Many researches in the past have proved that medical students experience elevated level of stress throughout their medical school life. Aims and Objective: The aim of the study is to study the prevalence and degree of stress among medical and dental students, find out the various stressors among them and the association of stress with various sociodemographic variables. Materials and Methods: A cross-sectional study was conducted among 159 medical and dental students of first and second year in Kist medical college and hospital. 81 medical and 78 dental students participated in the study. General Health Questionnaire (GHQ-12) and Medical students stress Questionnaire (MSSQ-40) was used. Statistical analysis was done by using SPSS version 25. Chisquare test was done to find the association of stress with various factors and to compare the degree of stress between medical and dental students. Results: Among 159 medical and dental students, 109 students (68.6%) were found to have stress. 48 out of 81 (59.3%) were medical students and 61out of 78 (78.2%) were dental students. Moderate stress was observed in 50/81(61.7%) medical students and 38/78 (48.7%) dental students. Similarly, high stress was observed in 10/81(12.3%) medical students and 11/78 (14.1%) dental students. Difference in the degree of stress between dental and medical students was not statistically significant (p value >.05). Academic related stress was the major source of stress in both medical and dental students. Gender, accommodation and motivation for study were found to be significantly associated with stress. Conclusions: The first two years of medical and dental students is stressful with academic related stress being the most prevalent stressor. Prevalence of stress was found to be more in dental students and the difference in the degree of stress between medical and dental students was not statistically significant.